Assessment cognitive functions in children with visual impairment by playing method - Statiev S. I. (Kharkov National Pedagogical University, 2010)
The cognitive functions of children are considered with paropsiss by a playing method. In research 10 children with a paropsis (experimental group) and 10 children (control group) took part without a paropsis. Age of children - 5-6 years. Directions are rotined adaptation of children to the environment. It is well-proven that a playing method gives the clear estimation of development of cognitive functions for children with paropsiss. In future a method allows to conduct rehabilitation measures on the improvement of the state of visual analyzer of children.